3log4(x^2+5x+6) ≤ 5 + log4((x+2)^3/(x+3))
[m]\left\{\begin {matrix}x^2+5x+6>0\\\frac{(x+2)^3}{x+3}>0\end {matrix}\right.[/m] ⇒ [m]\left\{\begin {matrix}(x+2)(x+3)>0\\\frac{(x+2)^3}{x+3}>0\end {matrix}\right.[/m] ⇒[red]x ∈ (- ∞;-3) U(-2;+ ∞)[/red]
[m]3log_{4}(x+2)(x+3) ≤5 log_{4}4+log_{4}\frac{(x+2)^3}{x+3}[/m]
[m]log_{4}((x+2)(x+3))^3 ≤ log_{4}4^5+log_{4}\frac{(x+2)^3}{x+3}[/m]
[m]log_{4}((x+2)(x+3))^3 ≤ log_{4}4^5\cdot \frac{(x+2)^3}{x+3}[/m]
Основание логарифмической функции 4 > 1.
Функция возрастает.
[m]((x+2)(x+3))^3 ≤4^5\cdot \frac{(x+2)^3}{x+3}[/m]
[m]((x+2)(x+3))^3 -4^5\cdot \frac{(x+2)^3}{x+3} ≤0 [/m]
[m](x+2)^3\cdot ((x+3))^3-\frac{1024}{x+3} )≤0[/m]
[m](x+2)^3\cdot (\frac{(x+3)^4-32^2}{x+3} )≤0[/m]
[m](x+2)^3\cdot (\frac{((x+3)^2-32)((x+3)^2+32)}{x+3} )≤0[/m]
[m](x+2)^3\cdot (\frac{((x+3)-\sqrt{32})((x+3)+\sqrt{32})}{x+3} )≤0[/m]
Решаем методом интервалов:
____+__ [-4sqrt(2)-3] ____-___ (-3) __+__ [-2]______-____ [4sqrt(2)-3] ____+___
C учетом ОДЗ: [red]x ∈ (- ∞;-3) U(-2;+ ∞)[/red]
о т в е т. [b][-4sqrt(2)-3;-3) U [-2;4sqrt(2)-3][/b]